Assessing the Impact of Face Recognition and QR Code-Based Attendance Systems on Payroll Processing and Business Efficiency - Fuady, Aflah Firduas; Hidayat, Ahmad Tri (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
Businesses have had to use new technologies to make their operations more efficient in the digital age, especially when it comes to managing their employees. This study examines the utilization of Face Recognition and QR Code technologies in a dual-mode attendance and payroll system to improve accuracy and efficiency in the management of attendance and payment processing. This research intends to examine the effects of this system on cutting down processing time, diminishing human errors, and enhancing overall cost effectiveness. The research utilized an experimental design with a case study methodology at PT TOTO SUKSES ABADI, where the system was evaluated and its performance assessed prior to and following installation. The results show that the dual-mode system cut down on the time it took to process payroll, got rid of human errors in attendance, and made the whole operation run more smoothly. Also, workers said they were happier since payroll handling was faster and more precise. The research indicates that the amalgamation of Face Recognition with QR Code technology can significantly improve the efficacy of human resource management